(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
A geometric morphometric study was conducted on the population of Polymesoda erosa in La Union, Cabadbaran City, to investigate the morphological variations using fluctuating asymmetry (FA) analysis. FA acts as a reliable indicator of ecological stress and developmental instability since it detects genetic or environmental changes that an organism experiences. A total of ninety (90) individual mud clams were randomly collected and analyze. Water and soil samples were also collected to gather data on the degree of body variations and the impact of external factors on P. erosa. The result of the analysis using the SAGE software revealed a highly significant fluctuating asymmetry (P 0.0001). Significant variations in individuals, sides, and the interaction between individuals and sides symmetry were mostly responsible for the substantial variances seen in mud clam species. Particularly, landmarks 10 (dorsal margin maxima) and 13 (anterior margin maxima) exhibited notable variations. For the water quality results, the mud clam’s internal valve was likely to be relatively unaffected or minimally impacted, but the level of nickel was high. In conclusion, the fluctuating asymmetry of P. erosa can be attributed to a stressed environment. Unfavorable environmental factors cause an organism’s morphology to change, affecting its symmetry.